A retrospective study of 30, 959 implants: Risk factors associated with early and late implant loss. (10th May 2018) - Lin, Guofen; Ye, Shuhua; Liu, Fengjia; He, Fuming
Abstract: Aim: This retrospective study assessed the risk factors associated with early and late implant loss at the patient‐ and implant‐based analysis. Materials and methods: A total of 18, 199 patients received 30, 959 dental implants during the years 2011–2015. Age, gender, jaw, location, implant brands, implant length and diameter, bone augmentation procedures, and the number of implants placed per patient were recorded. A multivariate generalized estimating equation (GEE) logistic regression was used to identify risk factors related to both early and late implant loss. Results: The cumulative survival rates were 98.0% for patients and 98.7% for implants after 1–6 years observation time. A total of 183 patients with 194 implants were lost before or at the abutment connection, and 193 patients with 209 implants were lost after occlusal loading of the implant fixture. The multivariable GEE logistic regression showed that males, patients aged ≥41 years, and mandibular anterior location were risk factors for early implant loss. In the case of late implant loss, males, patients aged ≥41 years, bone augmentation and short implants were correlated with a significantly increased failure rate. Conclusions: General factors such as male sex, elderly patients, mandibular anterior location, bone augmentation and short implants were associated with implant loss.